The role of microalgae in the bioeconomy - Acien, Gabriel (2021)
ABSTRACT: The bioeconomy is a new and essential paradigm for reducing our dependence on natural resources and responding to the environmental threats that the Earth is currently facing. In this regard, microalgae offer almost unlimited possibilities for developing a modern bioeconomy given their metabolic flexibility and high biomass output rates, even when produced under harsh conditions, such as when treating wastewaters or using flue gases. In this article, the microalgal contribution to important economic activities such as the production of food and feed, cosmetics and health-related compounds is reviewed. Moreover, potential contributions of microalgae to emerging sectors are discussed, as in the production of biomaterials, agriculture-related products, biofuels and provision of services such as wastewater treatment and the clean-up of industrial gases. The different microalgal production technologies have also been analyzed to identify the main bottlenecks affecting microalgal use in different applications. Finally, the major challenges facing microalgal biotechnology in enlarging its contribution to the bioeconomy are evaluated, and future trends discussed.